Virtual Reality Improves Patient Experience and Anxiety During In-office Carpal Tunnel Release. Issue 7 (13th July 2022) - Miller, McKenzie B.; Gabel, Shelley A.; Gluf-Magar, Lindsay C.; Haan, Pam S.; Lin, Judith C.; Clarkson, James H. W.
Abstract : Background: This study examined how wide- awake local anesthesia no tourniquet (WALANT) surgery in the office versus the standard operating room (OR) impacts patient experience, and the effect wide awake virtual reality (WAVR) has in conjunction with WALANT on patient experience. Methods: This is a patient-reported outcome study of patients undergoing carpal tunnel release by a single surgeon between August 2017 and March 2021. Patients were classified by location; traditional OR versus WALANT in-office. In-office patients were further classified by whether they chose to use WAVR or not. Patients rated overall experience, enjoyability, and anxiety using a Likert scale (1–7). Results: The online survey had a 44.8% response rate. OR patients were twice as likely to report a neutral or negative experience (23% versus 11%, P = 0.03), significantly lower enjoyment scores (44% versus 20%, P = 0.0007)‚ and higher anxiety (42% versus 26%, P = 0.04) compared with office-based WALANT patients. With the addition of WAVR, office patients reported higher enjoyment than those who did not use WAVR (85% versus 73%, P = 0.05). Patients reporting an anxiety disorder were more likely to choose WAVR when compared with patients without anxiety disorder (73.8% versus 56.4%). When they chose WAVR, they had greater anxiolysis (79% versus 47%, P = 0.01)‚ and increased enjoyment (90% versus 59%, P = 0.005). Conclusions: This study demonstrates improved patient experience in the office setting, further amplified by WAVR. Preexisting anxiety disorder is a positive predictive variable toward the patients' choice to use WAVR.